Implementation of Jakarta Pintar Card (KJP) (An Analysis of Education Policy) - Ahmad Zain Sarnoto,; Sri Tuti Rahmawati,; Rachmat Hidayat,; Saihu, (Technium Social Sciences Journal, 2020)
Education is one of the determining factors for the progress of the nation in the future. To create education that can support its progress, all components of the nation must be integrated and support education programs and policies. Jakarta Smart Card as a new breakthrough in the world of education in DKI Jakarta Province, comes as a support to invest in education. The purpose of writing this journal is to analyze the DKI Jakarta Provincial Government's policy in the form of providing Education assistance through the Jakarta Smart Card, both in terms of understanding, the amount of costs obtained and other benefits that can be enjoyed by the recipient of these funds. This research is a descriptive qualitative research in the form of literature study where the data collected will be analyzed which is supported by comprehensive observations regarding the existence of KJP, its essence and substance in improving the quality of education in DKI Jakarta to date. This study concludes that the involvement of the government in financing education is the right step in an investment towards a developed nation, with a record of being well managed and on target.